Temporal trends of in‐hospital complications associated with catheter ablation of atrial fibrillation in the United States: An update from Nationwide Inpatient Sample database (2011–2014). (30th March 2018) - Tripathi, Byomesh; Arora, Shilpkumar; Kumar, Varun; Abdelrahman, Mohamed; Lahewala, Sopan; Dave, Mihir; Shah, Mahek; Tan, Bryan; Savani, Sejal; Badheka, Apurva; Gopalan, Radha; Shantha, Ghanshyam Palamaner Subash; et al.
Abstract: Background: Catheter ablation is widely accepted intervention for atrial fibrillation (AF) refractory to antiarrhythmic drugs, but limited data are available regarding contemporary trends in major complications and in‐hospital mortality due to the procedure. This study was aimed at exploring the temporal trends of in‐hospital mortality, major complications, and impact of hospital volume on frequency of AF ablation–related outcomes. Methods: The Nationwide Inpatient Sample database was utilized to identify the AF patients treated with catheter ablation. In‐hospital death and common complications including vascular access complications, cardiac perforation and/or tamponade, pneumothorax, stroke, and transient ischemic attack, were identified using International Classification of Disease (ICD‐9‐CM) codes. Result: In‐hospital mortality rate of 0.15% and overall complication rate of 5.46% were noted among AF ablation recipients (n = 50, 969). Significant increase in complications during study period (relative increase 56.37%, P‐trend < 0.001) was observed. Cardiac (2.65%), vascular (1.33%), and neurological (1.05%) complications were most common. On multivariate analysis (odds ratio [OR]; 95% confidence interval [95% CI]; P value), significant predictors of complications were female sex (OR = 1.40; CI = 1.17–1.68; P value < 0.001), high burden of comorbidity as indicated by Charlson Comorbidity Index ≥2 (OR = 2.84; CI = 2.29–3.52; P value < 0.001), and low hospital volume (< 50 procedures). Conclusion: Our study noted a decline in AF ablation–related hospitalizations and complications associated with the procedure. These findings largely reflect shifting trends of outpatient performance of the procedure and increasing safety profile due to improved institutional expertise and catheter techniques.